The Role of Traceability of Standardized Palm Oil Seed for Strengthening Smallholder Plantation in Indonesia - Prasetya, Bambang; Tampubolon, Biatna Dulbert; Wahono, Daryono Restu; Darmayanti, Nur Tjahyo Eka; Kristiningrum, Ellia; Mulyono, Ary Budi; Aliyah, Novin; Isharyadi, Febrian; Ayuningtyas , Utari; Wulansari, Nuri; Susmiarni , Rika Dwi (Journal of Ecohumanism, 2025)
Oil palm has a very important economic value but also social-enviromental concern in several countries. Currently the top 5 world biggest producer are Indonesia 59%, followed by Malaysia 24%, Thailand 4%, Colombia 2% and Nigeria 2%. In Indonesia oil palm plantations continue to grow significantly which planted 3 difference companies (large private estate crop large state estate crop and small-holder estate crop). In terms of plantation management between large plantations and small plantations, there is a significant gap that affects the performance of small plantations. One of the most important factors to assurance the productivity of oil palm is availability of seed quality. Even though there are already standardization and regulations related to seed production, but the low quality or sub-standard seeds are still found on the market which are very detrimental, especially for smallholder. In this paper, traceability of palm oil seed in the system supply chain are reported based on the survey on around 80 percent of legally existing firms. The traceability are observed and various possibilities for the entry of sub-standard seeds into the market were analysed. Based on the facts, some recommendation are formulated to improve the effective conformity assessment to strengthen the small-holder plantation.